PERBEDAAN KUALITAS FRESH FROZEN PLASMA YANG DICAIRKAN DENGAN METODE KONVENSIONAL DAN DENGAN METODE ALAT FFP THAWER - Retno, Didin; Riza Zainal, Ahmad; D Machsoos, Budi; Heri Hermanto, Djoko; Oktya Wardhani, Shinta (journal of internal medicine; Vol. 13, No. 1 Januari 2012, 2014)
Saiful Anwar Hospital (SAH) doesn?t have standardized Fresh Frozen Plasma (FFP) liquefying tools. Standard Operating Procedure (SOP) to liquify FFP at SAH is put the FFP on the table until diluted. Recently a new Thawer of FFP was developed in SAH. In this study we compared between the two methods which are convensional and the new one. Thirtty two bag of FFP were divided in two different treatments which is group of new Thawer and the convensional. Each liqueed bag of FFP was recorded the time of liquefaction, aPTT, PPT and INR. Statistical analyses using independent T test or Mann-Whitney as alternative. In this study found mean time of liquefaction of FFP on Thawer group were shorter than conventional method 25.32 ± 3.4 vs 50.38 ± 5.52 minutes and statistically signicant (p < 0.05). Mean of aPTT on new Thawer group is 36.79 ± 5.94; but on conventional method is 36.94 ± 5.53 second (p = 0.67). Mean of PPT 11.71 ± 0.95 second on new Thawer group and 11.84 ± 2.22 second on conventional method (p = 0.249). Mean INR each group were 1.02 ± 0.08 on new Thawer group and 1.03 ± 0.19 on conventional method (p = 0.234). This study shows that new FFP Thawer liquifay FFP more quickly than conventional method without decreasing the quality of FFP.
Keywords: FFP, Thawer, conventional